Perbandingan Gradasi Butiran Sedimen Terendap Waduk Batujai dengan Material Bahan Kerajinan Gerabah Bukit Balibe - Saadi, Yusron; Tampang, Tampang; Salehudin, Salehudin; Suroso, Agus; Pradjoko, Eko; Estyana, Ema; Rohmayani, Hairun Nisak; Aslam, Firar Bismi; Supardi, Supardi; Ihsan, Ihsan; Aji, Eko Usman (LPPM Universitas Mataram, 2025)
Sediment deposition is the main problem in the continuity of dam operations. Sustainable operation of dam can be maintained by dredging sediment deposited at the bottom of the impounding area. Because of the considerable costs and the lack of economic value of dam deposited sediment, dredging is carried out only when the serious sedimentation problem occurs. This research aims to analyse samples of sediment taken from various depths of Batujai Dam and to compare them with the pottery materials of Balibe Hill. Compositions of deposited sediment were analyzed to determine its potential as an alternative additional material used in pottery making. Comparisons were made based on the results of sieving analysis of material from both sources. The results show that the percentage of fine-grain material of Balibe Hill, especially grains with a diameter of â‰¤ 0.18 mm, is closer to the percentage of deposited sediment of Batujai Dam at an elevation of 92.5 masl and an elevation of 90.0 masl, while the percentage of coarse-grain material with a diameter of â‰¥ 3.35 mm is closer to the percentage of deposited sediment at an elevation of 87.5 masl. Gradation analysis indicates that composition of deposited sediment of Batujai Dam in sand grain classes can be engineered to some extent to make them closely identical to the composition of Balibe Hill materials so that it can be used as a mixture in pottery making.